Corporate governance, IPO performance and politically-connected companies in Singapore. - Lim, Jiongting. (2008)
Political connections may contribute to the performance of newly listed companies. We investigate the board structure of newly listed companies in Singapore. We compare the market performance of newly listed companies with and without political connections. We show that Singapore listed companies with politically connected directors have better firm performance than non-politically connected companies. We also show that larger size offerings lead to the appointment of more politically connected directors and at the same time, more politically connected directors lead to a large IPO offering. However, there is no significant difference in the short term (first day) trading between the politically connected and non-politically connected companies.